Model Pembacaan Kontekstual Nasr Hamid Abu Zayd Terhadap Teks Suci Keagamaan (Al-Qur’an) - Farid Hasan; Siti Robikah (Institut Islam Nahdlatul Ulama Temanggung, 2020)
According to Amin al-Khuli, one of the figures who gives an effect to the thought of Nasr Hamid Abu Zaid on his study about al-Qur’an, at the first time, a thought of the Islamic modernity is considered as an infidelity by some people. As time goes by, they pursue it and the thought of it becomes Madzhab for them. Perhaps, that is a right term for Nasr Hamid, the Egyptian intellectual whose thought is regarded an infidelity in the beginning, but it becomes a popular object for the field of study and the research in the world academics, as happened in Indonesia. It is caused by the Nasr Hamid Abu Zaid’s concepts about Islamic modernity which can be considered as a new term in study discourse of al-Qur’an. Linguistics-Semantics and literature are the approaches offered by him in the study of al-Qur’an, because these approaches are capable to find the objective meaning of al-Qur’an, so the approaches, thought and interpretation of religious texts can be more dynamic, contextual, inclusive and relevant to the contemporary discourse of society. Based on the explanation, this study analyzes the views of Nasr Hamid about al-Qur’an and the ways of interpretation which is developed by him. It is hoped that we can see more objectively about who he is, so we don’t fall into a blind claims and maintaining a stagnation.